Pengaruh Terapi Contrast Bath (Rendam Air Hangat Dan Air Dingin) terhadap Oedema Kaki pada Pasien Congestive Heart Failure - Rizki Amelia; Silvia Nora Anggraini (STIKes Payung Negeri Pekanbaru, 2021)
Congestive Heart Failure (CHF) is the inability of the heart muscle to pump blood to meet the body's metabolic needs. Some patients with CHF generally experience edema of the lower extremities. Edema causes decreased health function and quality of life, discomfort, and changes in posture. One form of hypervolemia management is the Contrast Bath therapy, which is a treatment by alternating calf-length soaking of the feet using warm water followed by cold water. The purpose of this study was to determine whether there is an effect of Contrast Bath Therapy (Warm and Cold Water Soaking) on Foot Edema in Congestive Heart Failure Patients. The number of respondents was 16 people. This type of research is a quantitative study with a pre-experimental design and uses a one group pre-post test design in a desaign. Based on the bivariate analysis, the results of the paired sample T test can be seen where there is a difference in the effect of Contrast Bath therapy (soaking in warm and cold water) on changes in the size of the edema of the feet of CHF patients, with an average (mean) of 1.750 and a P value of 0.000 (<0 , 05). For further research, this study can be continued on the effect of family support on the psychological outpatients with CHF.